2013
DOI: 10.1542/peds.2012-3746
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dexamethasone for Bronchiolitis: A Randomized Trial

Abstract: OBJECTIVE: Determine whether dexamethasone treatment added to salbutamol reduces time to readiness for discharge in patients with bronchiolitis and possible asthma. METHODS: We compared efficacy and safety of dexamethasone, 1 mg/kg, then 0.6 mg/kg for 4 more days, with placebo for acute bronchiolitis in patients with asthma risk, as determined by eczema or a family history of asthma in a first-degree relative. All patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 32 publications
3
54
1
3
Order By: Relevance
“…88 Basic science studies focused on understanding the interaction between β agonists and corticosteroids have shown potential mechanisms for why simultaneous administration of these drugs could be synergistic. [89][90][91][92] However, other bronchiolitis trials of corticosteroids administered by using fixed simultaneous bronchodilator regimens have not consistently shown benefit [93][94][95][96][97] ; hence, a recommendation regarding the benefit of combined dexamethasone and epinephrine therapy is premature.…”
Section: Action Statement Profile Kas 4bmentioning
confidence: 99%
“…88 Basic science studies focused on understanding the interaction between β agonists and corticosteroids have shown potential mechanisms for why simultaneous administration of these drugs could be synergistic. [89][90][91][92] However, other bronchiolitis trials of corticosteroids administered by using fixed simultaneous bronchodilator regimens have not consistently shown benefit [93][94][95][96][97] ; hence, a recommendation regarding the benefit of combined dexamethasone and epinephrine therapy is premature.…”
Section: Action Statement Profile Kas 4bmentioning
confidence: 99%
“…Finally, oral dexamethasone (1 mg/kg on day 1, followed by 0.6 mg/kg for four additional days) given to hospitalized bronchiolitis patients who have eczema or a first degree family member with asthma shortened the duration of the hospitalization. 49 The results of these studies must be confirmed in additional trials before any change to the recommendation to not administer corticosteroids for viral bronchiolitis is considered.…”
Section: Acute Bronchiolitismentioning
confidence: 97%
“…In addition, the routine use of many common medications, including bronchodilators; corticosteroids; ribavirin; and antibiotics, and chest x-ray study have not been shown to be effective in improving the clinical course of the illness (4,5). Although some of the recommendations are controversial because a recent randomized controlled trial study and Cochrane systematic reviews showed that oral dexamethasone can reduce time to discharge from observation unit and nebulized epinephrine can reduce hospital admission rate, routine use of diagnostic tests, such as chest x-ray study, white blood count, and viral test are still not recommended (6,7). However, recent research has shown that emergency departments (EDs) continue to use nonrecommended practices in patients presenting with acute bronchiolitis (8).…”
Section: Introductionmentioning
confidence: 99%